Study of the Knautia arvensis herb carbohydrate composition - Burlaka , Vladyslav; Vladymyrova , Inna; Mykhailenko , Olha (Annals of Mechnikov's Institute, 2026)
Introduction. Knautia arvensis is a perennial Eurasian medicinal plant widely distributed in Europe, Ukraine, also found in regions of northwestern Africa and Asia. The identification and investigation of the quantitative content of polysaccharides (PS) in Knautia arvensis herb represent a relevant and timely research direction. Objective. Comparative determination of the quantitative content of polysaccharide fractions in Knautia arvensis herb, including water-soluble polysaccharides (WSPs), pectic substances (PS), and hemicelluloses (HC) A and B from different growth locations—Kharkiv and Vinnytsia regions—and identification and quantification of the monosaccharide composition of each polysaccharide fraction are the main aims of the study. Materials and methods. The object of the study was the aerial parts of Knautia arvensis, which were harvested in the Kharkiv and Vinnytsia regions at the beginning of the flowering stage (May–June 2025). The plant raw material was dried using an air-shade method at a temperature not exceeding 25 C. Results and discussion. As a result of the conducted studies, polysaccharide complexes of Knautia arvensis herb from different collection sites were fractionated for the first time. Their monomeric composition was identified. Their quantitative content was determined. Conclusions. Among the polysaccharide complex fractions of Knautia arvensis herb, the pectic substance (PS) fractions predominate, with a content of 8.77 ± 0.06% (for the sample from Vinnytsia Region) and 8.07 ± 0.12% (for the sample from Kharkiv Region). The obtained results on the fractional composition of the polysaccharide complex of Knautia arvensis herb will be used in the development of quality control methods for the medicinal plant raw material and the substances derived from it. The obtained results indicate the potential of Knautia arvensis herb for use in medical practice.